Influência da exposição solar sobre o perfil de metilação e hidroximetilação global de DNA e em sítios específicos no promotor dos genes miR-9-1, miR-9-3 e MTHFR em amostras de pele humana - Silva, Mikaelly Batista da (2016)
Epigenetics is the study heritable changes of in gene expression without modifications in the primary sequence of DNA. In our study we investigated the influence of sun exposure on global DNA methylation and hydroxymethylation status and at specific sites of the miR-9-1, miR9-3 and MTHFR genes in skin samples of subjects with no history of skin diseases. Skin biopsies were obtained by punch on sun-exposed and sun-protected arm areas from 24 corpses aged 16-89 years old from the Brazilian Service of Death Investigation. Genomic DNA was extracted from skin samples that were ranked according to Fitzpatrick’s criteria as light, moderate and dark brown. Global DNA methylation and hydroxymethylation and DNA methylation at specific sites analyses were performed using an ELISA and MSP, respectively. No significant differences in global DNA methylation and hydroxymethylation levels were found between the skin areas, skin type or age. However, gender-related differences were detected, where women showed higher methylation levels in comparison to those in men. Global DNA methylation levels were higher than hydroxymethylation levels, and the levels of these DNA modifications correlated in skin tissue. For specific sites, it was detected no differences among areas. Additional analyses showed no differences in the methylation status when age, gender and skin type were considered. We conclude that sun exposure does not induce changes in the global DNA methylation and hydroxymethylation status or at specific sites in the miR-9-1, miR-9-3 and MTHFR genes for skin types studied.